Development and initial validation of a theory of planned behavior questionnaire: Assessment of purchase intentions towards products associated with CRM campaigns - Parthesh R. Shanbhag; Yogesh P. Pai; Gururaj Kidiyoor; Nandan Prabhu (Cogent Business & Management, 2023)
This research develops and validates scales based on the theory of planned behavior (TPB) to measure purchase intention towards products associated with cause-related marketing (CRM) campaigns in the South Asian context. Despite few studies using global measures of TPB in specific contexts to predict behavioral intention towards CRM campaigns, this study develops and uses belief-based formative indicators that can be used as an intervention to bring about behavioral changes for positive campaign outcomes. A mixed methods approach was used, including focus group discussions and open-ended questionnaires, to collect qualitative data from 62 participants, resulting in the development of the formative indicators of the measurement instrument. The scales were then combined with global measures of reflective indicators and validated using data collected from 1035 respondents in a quantitative study. The results support the TPB theory and show that the scales have strong internal consistency, reliability, and validity. The findings indicate that behavioral beliefs (Ø = 0.834, p < 0.001), normative beliefs (Ø = 0.631, p < 0.001), and control beliefs (Ø = 0.725, p < 0.001) significantly impact attitude, subjective norm, and perceived behavioral control respectively. Attitude (Ø = 0.374, p < 0.001), subjective norms (Ø = 0.218, p < 0.001), and perceived behavioral control (Ø = 0.320, p < 0.001) significantly influence purchase intentions, with attitude having the most significant impact. The study also found that purchase intention significantly affects purchase behavior (Ø = 0030.530, p < 0.001). And therefore, this study strengthens the theory of planned behavior in the context of CRM campaigns, aligning with the broader field of ethical consumption.
Keywords: 650; Cause-related marketing; ethical marketing; mindful consumption; scale development; theory of planned behavior